Prevalence and Risk Factors of Anemia in Pregnant Women in Najaf Governorate, Iraq: A Study in Primary Health Care Centers. - Ahmad Maki; Mohammed Farhan Shahad; Waleed Mohammed Abd; Ameer Ali Hussein; Redha Hassan Ali; Samir Akmoush Dakhel; Saad Rahim Sultan; Karar Salman Suwaid (Genius Journals, 2023)
Anemia is a prevalent public health concern that affects individuals in both developed and developing countries. A significant portion of pregnant women worldwide are anemic, which can have significant negative impacts on maternal, fetal, and infant health. The purpose of this study is to investigate the prevalence and risk factors of anemia among pregnant women in Najaf Governorate, Iraq. A sample of 2227 pregnant women who visited primary health care centers in Najaf Governorate were analyzed for the presence, type, and risk factors associated with anemia. The overall prevalence of anemia among pregnant women was found to be 41%. This study highlights the high prevalence of anemia among pregnant women in Najaf Governorate, and emphasizes the need for anemia prevention and control strategies, as well as educational programs, particularly in rural areas.
Keywords: Pregnancy-associated Anemia; Automated Hematological Analyzer; Predisposing Factors,; Hemoglobin